Prognostic markers of sarcoidosis: an analysis of patients from everyday pneumological practice - Doubková, Martina; Pospíšil, Zdeněk; Skřičková, Jana; Doubek, Michael (The clinical respiratory journal, 2015)
INTRODUCTION: Although sarcoidosis is a well-known disease, sarcoidosis patient outcome and the role of prognostic markers in everyday practice have not yet been well described. Therefore, the goal of the present study was to analyse the fate of sarcoidosis patients and the factors influencing the disease's behaviour in routine practice. METHODS: The study was a retrospective analysis of 306 consecutive patients (181 females and 125 males; median age 45 years) diagnosed with sarcoidosis in the years 2003-2012. RESULTS: Through the use of uniparametric analysis, it was determined that the stage of the disease, organ involvement, CD4/CD8 ratio in the bronchoalveolar lavage fluid (BALF), serum and urine calcium levels, smoking, and pulmonary functions had a significant influence on spontaneous sarcoidosis resolution. Multiparametric analysis revealed that spontaneous resolution was significantly positively influenced by female gender, a less advanced disease stage, a higher CD4/CD8 ratio in the BALF, lymphocytosis in the BALF and normal pulmonary functions at diagnosis. During follow-up, only three patients died. The causes of death were respiratory failure with pneumonia (n = 2) and heart attack caused by sarcoidosis heart involvement (n = 1). CONCLUSION: The data show sarcoidosis as a disorder with high variability in clinical and laboratory findings but with good general prognosis.
Keywords: senioři; Retrospective Studies; Prognosis; Sarcoidosis; prognostic factors; sexuální faktory; Middle Aged; mužské pohlaví; CD4-CD8 Ratio; Adult; mladý dospělý; poměr CD4 a CD8 lymfocytů; bronchoalveolární lavážní tekutina; Young Adult; ženské pohlaví; prognóza; retrospektivní studie; Humans; therapy; Sex Factors; sarkoidóza; Bronchoalveolar Lavage Fluid; lidé středního věku; diagnosis; sarcoidosis; dospělí; Female; Aged; lidé; Male